Congenital alterations from a triplet pregnancy with opposite sex conceptuses in cattle associated with reproductive biotechnologies (Research, Society and Development, 2022)
Livestock in Brazil is still characterized by low zootechnical rates. Through these perspectives, research on reproductive biotechnologies has increased with the aim of reversing this scenario to ensure high reproductive efficiency in herds. The main biotechnologies applied to bovine reproduction include artificial insemination (AI), fixed-time artificial insemination (FTAI), superovulation (SOV) and embryo transfer (ET) and in vitro embryo production (IVP). The FTAI is highly recommended in the field due to its high rate of reproductive performance. To perform this technique, it’s necessary to use hormones such as estrogenic esters, prostaglandin, equine chorionic gonadotropin (eCG) and progesterone. Due to the long half-life of this hormone, the eCG can lead to the occurrence of multiple ovulations generating twin births. By this, the aim of this study was to report a case of a freemartin heifer, with patent urachus, from a triplet pregnancy resulting from artificial insemination. At first evaluation, the heifer presented inappetence, weight loss, cachexia, dehydration, prostration, pale oral and ocular mucosa, temperature of 39.5°C and diarrhea. In the evaluation of the extracavitary umbilical structures, it was noted that the urine was excreted through the vulva and the umbilicus and the site had an increase in volume. After a day in the hospital, the animal died. At necropsy, it was found the absence of female sexual organs such as uterus and ovaries and in the abdominal region, presence of fluid in the cavities (ascites and hydrothorax) were observed. The suspected death cause was ureter stenosis that led to uremia.